Knowing that strawberries are red and seeing red strawberries: the interaction between surface colour and colour knowledge information. Issue 6 (17th August 2016) - Bramão, Inês; Reis, Alexandra; Petersson, Karl Magnus; Faísca, Luís
ABSTRACT: This study investigates the interaction between surface and colour knowledge information during object recognition. In two different experiments, participants were instructed to decide whether two presented stimuli belonged to the same object identity. On the non-matching trials, we manipulated the shape and colour knowledge information activated by the two stimuli by creating four different stimulus pairs: (1) similar in shape and colour (e.g. TOMATO–APPLE); (2) similar in shape and dissimilar in colour (e.g. TOMATO–COCONUT); (3) dissimilar in shape and similar in colour (e.g. TOMATO–CHILI PEPPER) and (4) dissimilar in both shape and colour (e.g. TOMATO–PEANUT). The object pictures were presented in typical and atypical colours and also in black-and-white. The interaction between surface and colour knowledge showed to be contingent upon shape information: while colour knowledge is more important for recognising structurally similar shaped objects, surface colour is more prominent for recognising structurally dissimilar shaped objects.